Reduced Expression of Glycerol-3-phosphate dehydrogenase (Gpdh) in Drosophila melanogaster Pasha-Mutants Suggests a miRNA-dependency in its Regulation - Najat Dzaki; Ghows Azzam (Tropical Life Sciences Research, 2019)
In Drosophila, the Glycerol-3-phosphate dehydrogenase (Gpdh) enzyme plays an active role in many pathways, including the glycerol metabolic pathway and the alpha-glycerophosphate cycle. It is also important for ethanol metabolism, as well as flight muscle development. Recent years have exposed small RNAs as a major posttranscriptional regulator of multiple metabolic-pathway genes. Of the many kinds of these RNAs at work, micro RNAs (miRNAs) are the most widely implicated and well understood. However, the roles they may play in regulating Gpdh has never been shown in any model organism. In this study, a pasha-mutant D. melanogaster strain was found to express only 25% of the Gpdh levels typical of their wild type counterparts. Such mutants lack the ability to produce pasha, a protein integral during miRNA-processing, and as a consequence do not produce mature miRNAs. As miRNA-centric regulation often culminates in the depletion of their targets, the concurrent downregulation of Gpdh observed in their absence here therefore alludes to two possibilities: one, that rather than being explicitly bound and repressed by miRNAs, Gpdh expression relies on their action upon an upstream Gpdh-antagonist; or two, that Gpdh may come under the regulation of another class of miRNA-like elements called mirtrons, which do not require pasha to be processed into their functional form. The preliminary findings in this study further highlights the imperative nature of miRNAs in regulating metabolic processes and subsequently, ensuring proper organismal development and its continued survival. Enzim Glycerol-3-phosphate dehydrogenase (Gpdh) dalam Drosophila memainkan peranan yang aktif dalam berbilang laluan, termasuk laluan metabolik gliserol dan kitaran alfa-gliserofosfat. Ia juga penting untuk metabolisma etanol, dan juga perkembangan otot penerbangan. Tahun-tahun kebelakangan ini telah mendedahkan RNA kecil sebagai pengatur pasca transkripsi utama bagi pelbagai metabolik-jalur gen. Daripada pelbagai jenis RNA, RNA mikro (miRNA) adalah yang paling banyak dikaitkan dan difahami dengan baik. Walau bagaimanapun, peranan yang didapati dalam mengawal Gpdh tidak pernah ditunjukkan dalam mana-mana organisma model. Dalam kajian ini, ketegangan pasha-mutan D. melanogaster didapati hanya menyatakan 25% daripada tahap Gpdh yang tipikal dari rakan-rakan jenis liar mereka. Mutan tersebut tidak mempunyai keupayaan untuk menghasilkan pasha, protein yang penting semasa pemprosesan miRNA, dan akibatnya tidak menghasilkan miRNA yang matang. Oleh sebab peraturan-peraturan yang berorientasi miRNA seringkali memuncak dalam penumpukan sasaran mereka, pengunduran Gpdh yang seragam yang diamati dengan ketiadaan mereka di sini merujuk kepada dua kemungkinan: satu, yang bukannya secara jelas terikat dan ditindas oleh miRNA, ekspresi Gpdh bergantung kepada tindakan mereka antagonis Gpdh hulu; atau dua, bahawa Gpdh mungkin berada di bawah peraturan kelas lain seperti miRNA yang dikenali sebagai mirtron, yang tidak memerlukan pasha diproses menjadi bentuk fungsinya. Penemuan awal dalam kajian ini seterusnya menonjolkan sifat penting miRNA dalam mengawal proses metabolik dan seterusnya, memastikan pembangunan organisma yang betul dan kelangsungan hidupnya yang berterusan.